Conceptualising conflicts between student participation and other rights and interests. Issue 2 (4th March 2021) - Perry-Hazan, Lotem
ABSTRACT: This paper delineates the conflicts that can arise between student participation and other rights and interests and presents a model that conceptualises these conflicts. It fills a gap in the developing literature on participation rights in education, which has yet to systematically address the possible ramifications of practices that implement these rights. The paper describes how students' participation may constrain various other children's rights: the right not to participate, not to be discriminated against, and to be protected from violence and abuse. In addition, it discusses possible clashes between the one-size-fits-all model of student participation and the rights of children and parents to culturally adaptable education. The paper also analyses how neoliberal practices of participation, such as high-stake student perception surveys, may undermine the social interest to empower teachers, which is intertwined with children's best interests and their right to education.